Implementation of Training Management to Improve the Quality of Education and Learning - Abdul Fattah Nasution; Wardatun Thaibah Marpaung; Uswatun Hasanah; Sifa Maulida (Manajia: Journal of Education and Management, 2024)
The quality of education/learning is an important factor in achieving national education goals. One effort to improve the quality of education/learning is to implement effective training management. It is hoped that quality training can improve the competence of teachers and other education personnel, thereby having an impact on improving the quality of learning in the classroom. This research aims to analyze the implementation of training management in schools/educational institutions and determine its effect on the quality of education/learning. This research uses qualitative methods with data collection techniques through interviews, observation and documentation. The research results show that the implementation of training management in schools/educational institutions is still not optimal. This can be seen from several aspects, such as training planning that has not been directed and has not involved all related parties. Furthermore, the implementation of training has not been effective, with methods and materials that do not suit the needs of participants. As well as inadequate evaluation of training, the effectiveness of training in improving the quality of education/learning is not yet known. The findings of this research indicate that improvements need to be made in the implementation of training management in schools/educational institutions. These improvements need to be carried out comprehensively, starting from planning, implementation, to training evaluation. By implementing effective training management, it is hoped that the quality of education/learning in schools/educational institutions can increase.